Off-label application of intravenous immunoglobulin (IVIG) for treatment of Cogan's syndrome during pregnancy. Issue 10 (10th October 2019) - Scherg, Felix; Haag, Friedrich; Krieger, Thorsten
Abstract : We report the case of a woman with Cogan's syndrome concomitant with the wish to have children. After three major flares of the disease that led to unilateral deafness, immunosuppressive therapy with prednisolone and azathioprine was started. Because of the severe side effects, an off-label therapy with intravenous immunoglobulin (IVIG) was initiated, under which our patient has since given birth to three healthy children. To our knowledge this is the first report to describe Cogan's syndrome with multiple successful pregnancies under IVIG treatment.